National identity and historic collective memory in Peru. An exploratory study - Rottenbacher, Jan Marc (2010)
We analyze the memory of collective events in Peru and its relationship with Peruviannational identity in a middle-class sample from Lima (N = 81). Peruvian collective self- esteem and two dimensions of the Peruvian self-concept (Peruvians as proactive-capable and negative image of Peruvians) are related moderately to valence of historic characters remembered. Nevertheless, valence of remembered historical events was not associated to Peruvian national identity. Results also suggest that characters and events from 20th century comprise the majority of remembered instances, and 20th century instances are worse evaluated than characters and events from previous periods of Peruvian history. Results confirm a recency bias and a tendency to make more positive meaning attributions to distant eventsand characters than those made to more recent events.